Tra comunità e società: La Casa del popolo e l'associazionismo nella Ponticelli del Novecento - Antonio Borrelli (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2019)
Associationism is a phenomenon has characterized the history of Ponticelli from the last years of 19th century until today. Since the end of the Second World War, for about three decades, the Italian Communist Party and, generally, the Left had a hegemonic role in the civil life of this Naples district of ancient farming and working-class traditions. In this context, in 1974, the House of People was born, which became the symbolic place of Neapolitan communists and the center of cultural initiatives with national resonance. Conferences, art exhibitions, theatrical and educational workshops were organized and directed by: «committed teachers», «avant-garde directors» and «aesthetic operators», that is, by intellectuals with an organic civil life reform project of the geographical and social suburbs. The crisis of Left Parties has led to a progressive rarefaction of the House of People's activities, but not to the end of its spirit, as shown by the Arci Movie Association. The association, born in 1990, is still engaged in the diffusion of film culture inside and outside Ponticelli. In this book it is possible to trace facts and people of this recent cultural and political season, which has suddenly faded in the collective memory, with the goal to contain its disintegration also manifested in the loss of documentary tracks